Design of Microwave LNA Based on Ladder Matching Networks for WiMAX Applications - Abu Bakar Ibrahim; Ahmad Zamzuri Mohamad Ali (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Advancement in the wireless industry, internet access without borders and increasing demand for high data rate wireless digital communication moving us toward the optimal development of communication technology. Wireless communication is a technology that plays an important role in current technology transformation. Broadband communication is a method of telecommunication that are available for transmitting large amounts of data, voice and video over long distance using different frequencies. Specifically, Low Noise Amplifier which is located at the first block of receiver system, makes it one of the important element in improving signal transmition. This study was aimed to design a microwave Low Noise Amplifier for wireless application that will work at 5.8 GHz using  high-performance low noise superHEMT transistor FHX76LP manufactured by Eudyna Technologies. The low noise amplifier (LNA) produced gain of 16.8 dB and noise figure (NF) of 1.20 dB. The input reflection (S11) and output return loss (S22) are -10.5 dB and -13.3 dB respectively. The bandwidth of the amplifier recorded is 1.2 GHz. The input sensitivity is compliant with the IEEE 802.16 standards.